The cost of phasing out nuclear power: a quantitative assessment of alternative scenarios for Germany - Christoph Böhringer; Tim Hoffmann; Stefan Vögele (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2000)
In the debate on the premature phase-out of nuclear power generation in Germany, there is an intense dispute on the effective operating time for the existing nuclear power plants. This paper addresses the question of how alternative phase-out regulations affect both the magnitude of total economic costs and the distribution of these costs across nuclear power plants and competing companies. Based on a dynamic partial equilibrium analysis of power supply options, we quantify the excess costs of different regulatory approaches as a function over time and investigate the implied competitive effects at the plant as well as at the company level. We find that alternative phase-out regulations which effectively lead to the same date for an ultimate shutdown of nuclear power generation exhibit large differences in total costs. The competitive distortions across companies also vary considerably with the chosen regulation depending on how the respective cost implications at the plant level get distributed at the company level via the specific ownership. Our quantitative results refer to nuclear phase-out scenarios for Germany and its specific plant structure as well as plant-ownership by companies. However, the issues and methodological approaches presented in this paper may be important for other industrialized countries which also contemplate a premature nuclear phase-out.
Keywords: 330; Kernenergiepolitik; Wirtschaftspolitische Wirkungsanalyse; Energieversorgung; Soziale Kosten; Elektrizitätswirtschaft; Kosten; Deutschland